The Joint Association of Small for Gestational Age and Nighttime Sleep with Blood Pressure in Childhood - Wang, Hongjian (Sci Rep, 2018)
Children born small for gestational age (SGA) are more likely to develop high blood pressure. In prior studies, longer sleep duration is associated with lower BP, and SGA is associated with shorter sleep duration in childhood. We investigated whether sleep duration in early childhood modifies the association between SGA and higher childhood SBP in 1178 children recruited at birth and followed up to age 9 years. We ascertained birthweight and gestational age from medical records. We derived child sleep duration from maternal questionnaire interview. We calculated child SBP percentile according to U.S. reference data. We defined elevated SBP as SBP ≥75(th) percentile. In this sample, 154 (13.1%) children were born SGA. Children born SGA had higher SBP percentiles and higher risk of elevated SBP. Among children born SGA, those in the highest compared to the lowest tertile for sleep had a 12.28 lower (−22.00, −2.57) SBP percentile and 0.44 (0.25 to 0.79) times lower risk of developing elevated SBP. Our data are consistent with an interaction between SGA and sleep duration on childhood elevated SBP (P(interaction) = 0.0056). In conclusion, in this prospective birth cohort, longer sleep duration in early childhood may mitigate the blood pressure-raising effect of being born small.